Dissemination des informations et conseils climatiques dans le domaine de l'elevage au Senegal - Kebe, Ndeye Amy; Fall, Serigne; Seck, Babacar; Ouedraogo, Issa; Siagbe, Golli (2024)
The Livestock and Climate Initiative, through its partnership with Jokalante, has made significant strides in disseminating weather and agropastoral advisory services in Senegal. With a focus on addressing the needs of agro-pastoralists in four key departments, the initiative has leveraged mobile technology, interactive radio broadcasts, and data-driven advisory services to improve the decision-making capacity of pastoralists. By fostering partnerships with local and national stakeholders such as ANACIM, MWGs, and community radio stations, the program has made progress in building a resilient, sustainable, and inclusive climate information ecosystem. While there are challenges related to profiling, connectivity, and MWG functionality, the groundwork has been laid for scaling up CIS dissemination. Strengthening partnerships, enhancing radio programming, and fostering the participation of pastoralist communities will be essential for future success.